Nanostructured films, pellicles, and methods for performing EUV lithography
Patent Information
- Application Number
- JP2023198661
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-16
- Filing Date
- 2023-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-09-15
Smart Images

Figure 0007635346000002 
Figure 0007635346000003 
Figure 0007635346000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates generally to thin films and thin film devices used in semiconductor microchip manufacturing, and more particularly to ultra-thin, ultra-low density nanostructured, free-standing pellicle films for extreme ultraviolet (EUV) lithography. [Background technology]
[0002] A pellicle is a protective cover over a photomask, used in semiconductor microchip manufacturing. A photomask may refer to an opaque plate with holes or transparencies that allow light to shine through a defined pattern. Such photomasks may be widely used in photolithography and integrated circuit manufacturing. As a master template, the photomask is used to generate patterns on a substrate (usually a thin slice of silicon known as a wafer in semiconductor chip manufacturing).
[0003] Particle contamination can be a significant problem in semiconductor manufacturing. Photomasks are protected from particles by a pellicle, a thin transparent film stretched over a mounted frame covering the patterned side of the photomask. The pellicle is close to the mask but far enough away that small to medium sized particles that land on the pellicle are too out of focus to be printed. In recent years, the microchip manufacturing industry has realized that pellicles can protect photomasks from damage resulting from sources other than particles and contaminants.
[0004] Extreme ultraviolet lithography is an advanced optical lithography technique that uses the EUV wavelength range (more specifically, 13.5 nm wavelength). It allows semiconductor microchip manufacturers to pattern the most delicate features at resolutions of 7 nm or less to place more transistors without increasing the size of the space required. EUV photomasks work by reflecting light. The reflection of light is achieved by using multiple alternating layers of molybdenum and silicon. When the EUV light source is turned on, the EUV light first strikes the pellicle, passes through it, and then reflects back from underneath the photomask, striking the pellicle once more, before continuing its path to print the microchip. During this process, some of the energy is absorbed, which can result in heat being generated, absorbed, and stored. The temperature of the pellicle can rise to 600-1000 degrees Celsius or higher.
[0005] While heat resistance is important, the pellicle must also be highly transparent to EUV to ensure the passage of reflected light and the light pattern from the photomask.
[0006] In 2016, a polysilicon-based EUV pellicle was developed after decades of research and efforts, but the EUV transmittance was only 78% for a simulated relatively low-power 175 watt EUV source. Driven by the desire for increased transistor density, stringent requirements present EUV pellicle developers with additional technical challenges for higher transmittance, lower transmittance variation, higher temperature tolerance, and stronger mechanical strength.
[0007] Attempts have been made to target higher light transmittance by placing a high single-wall carbon nanotube content (e.g., as high as 98% by weight) in the carbon nanotube sheet, but such attempts have resulted in products with poor structural quality and reduced mechanical strength and / or durability. Thus, such carbon nanotube-based thin films need to be provided with a certain level of thickness to support their structural integrity. As a result, the EUV transmittance of such carbon nanotube-based thin films still does not meet industry standards. Thus, in conventional technology, the transmittance of EUV light and the thickness of the pellicle film have been limited from further advancement. Summary of the Invention
[0008] According to an aspect of the present disclosure, a specifically structured nanostructured film is disclosed, the nanostructured film comprising a plurality of carbon nanofibers randomly crossing to form an interconnected network structure in a planar orientation, the interconnected network structure having a thickness ranging from a lower limit of 3 nm to an upper limit of 100 nm and a plurality of pores, the plurality of carbon nanofibers including single-walled carbon nanotubes, multi-walled carbon nanotubes, and at least 50% double-walled carbon nanotubes, the number of walls of the single-walled carbon nanotubes being 1, the number of walls of the double-walled carbon nanotubes being 2, and the number of walls of the multi-walled carbon nanotubes being 3 or more.
[0009] According to another aspect of the disclosure, in some embodiments, the thickness has a lower limit of 3 nm to an upper limit of 40 nm.
[0010] According to another aspect of the disclosure, in some embodiments, the thickness has a lower limit of 3 nm to an upper limit of 20 nm.
[0011] According to yet another aspect of the present disclosure, in some embodiments, the average thickness of the interconnected network structure is 11 nm.
[0012] According to further aspects of the present disclosure, in some embodiments, EUV transmission is increased to greater than 95%.
[0013] According to yet another aspect of the present disclosure, in some embodiments, EUV transmission is increased to greater than 98%.
[0014] According to a further aspect of the present disclosure, the plurality of carbon nanofibers further comprises single-walled carbon nanotubes and multi-walled carbon nanotubes, wherein the single-walled carbon nanotubes have one wall, the double-walled carbon nanotubes have two walls, and the multi-walled carbon nanotubes have three or more walls.
[0015] According to another aspect of the present disclosure, single-walled carbon nanotubes comprise 20-40% of all carbon nanotubes, double-walled carbon nanotubes comprise 50% or more of all carbon nanotubes, and the remaining carbon nanotubes are multi-walled carbon nanotubes.
[0016] According to a further aspect of the present disclosure, single-walled carbon nanotubes comprise greater than 20% but less than 50% of all carbon nanotubes, double-walled carbon nanotubes comprise greater than 75% of all carbon nanotubes, and the remaining carbon nanotubes are multi-walled carbon nanotubes which comprise the remaining percentage of all carbon nanotubes.
[0017] According to another aspect of the present disclosure, any two EUV transmission measurements from the same nanostructured film at any focal region differ by less than 5%.
[0018] According to another aspect of the present disclosure, any two EUV transmittance measurements from the same nanostructured film at any focal region differ by less than 2%.
[0019] According to another aspect of the present disclosure, any two EUV transmission measurements from the same nanostructured film at any focal region differ by less than 0.4%.
[0020] According to another aspect of the disclosure, the network (particularly for EUV lithography applications or lithography scanners) has a distortion of less than 3.5 mm under constant 2 Pa pressure, under a flow rate of 10 sccm, under a flow rate of 8 sccm, under 3.5 mbar / sec, or under any scanner conditions.
[0021] According to another aspect of the present disclosure, the distortion is less than 0.6 mm under a constant 2 Pa pressure, a flow rate of 10 sccm, a flow rate of 8 sccm, 3.5 mbar / sec, or under any scanner condition.
[0022] According to another aspect of the present disclosure, the network (particularly for EUV lithography applications or lithography scanners) has a distortion of less than 0.1 mm for a full size EUV pellicle (approximately 110x144 mm, 2.5 mm gap from reticle in scanner) when subjected to a pumping down speed of 3.5 mbar / sec.
[0023] According to another aspect of the present disclosure, the network has a strain of less than 0.1 mm under a flow rate of 3.5 mbar / sec.
[0024] According to another embodiment of the present disclosure, the network exhibits less than 0.3% scattering under EUV irradiation.
[0025] According to another aspect of the present disclosure, the nanofibers are conformally coated with a metal, metal oxide, or nitride, where the metal is selected from boron, ruthenium, zirconium, niobium, molybdenum, rubidium, yttrium, strontium, or rhodium.
[0026] According to another aspect of the present disclosure, the nanostructured film has an areal density of about 0.2 μg / cm 2 ~Approx. 6.0μg / cm 2 It is.
[0027] According to an aspect of the present disclosure, a pellicle is disclosed, the pellicle including a pellicle boundary defining an opening, and at least one nanostructure film attached to the pellicle boundary and covering the opening.
[0028] According to another aspect of the present disclosure, a method of performing EUV lithography is disclosed, the method including transmitting EUV radiation through a pellicle.
[0029] The present disclosure will be further described in the following detailed description with reference to a number of drawings, which are mentioned as non-limiting examples of preferred embodiments of the present disclosure, in which like characters represent like elements throughout the several views of the drawings. [Brief description of the drawings]
[0030] [Figure 1] 1A-1D illustrate a filtration method for forming a pellicle film according to an exemplary embodiment. [Diagram 2] FIG. 2 illustrates different types of CNT compositions and their mechanical properties in Samples A to I according to a typical embodiment. [Figure 3A] FIG. 1 illustrates a scanning electron microscope (SEM) image of the microstructure of a DWCNT film according to an exemplary embodiment. [Figure 3B] FIG. 1 illustrates areal density according to an exemplary embodiment. [Figure 4A] FIG. 1 illustrates the transparency and absorbance of DWCNT films at 550 nm for different areal densities according to an exemplary embodiment. [Figure 4B] FIG. 1 illustrates the effect of areal density on strain at 2 Pa as well as burst and permeability of a 25x25mm sized DWCNT film according to an exemplary embodiment. [Figure 4C] FIG. 13 illustrates the effect of DWCNT / MWCNT ratio on CNT film strain at 2 Pa and rupture for films 25x25 mm and areal densities from 2.9 to 3.0 μg / cm2. [Figure 4D]FIG. 13 illustrates the distortion of a film 110x140mm and 0.65 μg / cm2 areal density during pumping down at a maximum rate of 3.5 mbar / sec according to an exemplary embodiment. [Figure 4E] FIG. 1 illustrates the effect of different DWCNT / MWCNT ratios on the burst pressure of CNT films. [Figure 5A] FIG. 1 illustrates a linear map of EUV transparency for two 0.6 μg / cm2 films 1×1 cm2 size according to an exemplary embodiment. [Figure 5B] FIG. 13 illustrates linear maps of EUV reflectance for two 0.6 μg / cm2 films 1×1 cm2 size according to an exemplary embodiment. [Figure 6A] FIG. 1 illustrates a set of bar graphs showing CNT bundle diameters for different samples of DWCNT-major composition films in accordance with an exemplary embodiment. [Figure 6B] FIG. 1 illustrates a set of bar graphs showing the major pore axes of different samples of DWCNT multi-composition films in accordance with an exemplary embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Through one or more of its various aspects, the embodiments and / or specific features or subcomponents of the present disclosure are intended to demonstrate one or more of the advantages specifically mentioned above and below.
[0032] A pellicle may refer to a thin, transparent film that protects a photomask during semiconductor microchip manufacturing. A pellicle may act as a dust cover to prevent particles and contaminants from falling onto the photomask during manufacturing. However, the pellicle must be transparent enough to allow light to pass through for lithography to occur. A higher level of light transmission is required for more effective lithography.
[0033] Furthermore, pellicles for EUV lithography require large (e.g., greater than 110x140mm) free-standing thin-film materials with extreme and unique properties. In addition to being highly transparent to EUV radiation, they must be resistant to temperatures in excess of 600°C, mechanically robust, and able to withstand handling, transportation, pumping down, and venting operations during the photolithography process. Gas permeability, yet the ability to retain micrometer-sized particles, is also desirable. Given the number of high-level properties required, effective EUV pellicles have traditionally been difficult to manufacture.
[0034] In this aspect, carbon nanotubes are proposed as a possible starting material for forming pellicles for this EUV pellicle application due to their excellent thermal and mechanical properties and ability to form porous films.
[0035] Carbon nanotubes and carbon nanotube films Carbon nanotubes (CNTs) typically come in several different varieties, including, but not limited to, single-walled CNTs (SWCNTs), double-walled CNTs (DWCNTs), multi-walled CNTs (MWCNTs), and coaxial nanotubes. They may exist substantially purely of one variety, or often in combination with other varieties. Individual CNTs may intersect with several others. Collectively, many CNTs can form mesh-like free-standing microstructured thin films. While such formation is possible, it may not be a guarantee in all endeavors, especially when making ultra-thin films with high EUV transparency. As the names suggest, SWCNTs have one or a single wall, DWCNTs have two walls, and MWCNTs have three or more walls.
[0036] Furthermore, among several possible methods to produce free-standing films, a filtration-based approach was used to produce films ranging from small size to films large enough and uniform for EUV pellicles. This filtration-based method allows for the rapid production of films of CNTs as well as other high aspect ratio nanoparticles and nanofibers (e.g., boron nitride nanotubes (BNNTs) or silver nanowires (AgNWs)). Because this approach separates the nanoparticle synthesis method from the film production method, different types of nanotubes made by virtually any method may be used. Different types of nanotubes can be mixed in any desired ratio. Filtration is a self-leveling process in the sense that non-uniformities in film thickness during the filtration process are self-corrected by local permeability variations, and is therefore a highly desirable film formation process and a promising candidate for the production of highly uniform films.
[0037] FIG. 1 illustrates a filtration method for forming a pellicle film according to an exemplary embodiment.
[0038] As illustrated in Figure 1, a free-standing carbon nanotube-based pellicle film may be created by a filtration-based method. In operation 101, a catalyst is removed from carbon nanotubes (CNTs) to be used to form an aqueous suspension. In an example, the CNTs may be chemically purified to reduce the concentration of catalyst particles to less than 1 wt% or preferably less than 0.5 wt% as measured by thermogravimetric analysis prior to dispersion in the suspension. The removal of the catalyst is not limited to any particular process or procedure, and any suitable process may be used to achieve the desired results.
[0039] In operation 102, an aqueous suspension is prepared using the purified CNTs such that the purified CNTs are uniformly dispersed within the aqueous suspension. When preparing one or more CNT suspensions, the carbon nanotube material can be mixed with a selected solvent to uniformly disperse the nanotubes within the final solution as a suspension. Mixing can include mechanical mixing (e.g., using a magnetic stir bar and stir plate), ultrasonic mixing (e.g., using an immersion ultrasonic probe), or other methods. In some examples, the solvent can be a protic or aprotic polar solvent, such as water, isopropyl alcohol (IPA), and aqueous alcohol mixtures, such as 60, 70, 80, 90, 95% IPA, N-methyl-2-pyrrolidone (NMP), dimethyl sulfide (DMS), and combinations thereof. In examples, a surfactant can also be included to aid in the uniform dispersion of the carbon nanofibers within the solvent. Examples of surfactants include, but are not limited to, anionic surfactants.
[0040] Carbon nanofiber films are typically formed from one of MWCNTs, DWCNTs, or SWCNTs. Carbon nanofiber films may also include mixtures of different types of CNTs (i.e., SWCNTs, DWCNTs, and / or MWCNTs) with varying ratios between the different types of CNTs.
[0041] Each of these three different types of carbon nanotubes (MWCNT, DWCNT, and SWCNT) has different properties. In one example, single-walled carbon nanotubes can be more conveniently dispersed in a solvent (i.e., most of the nanotubes are suspended separately and are not adsorbed onto other nanotubes) for subsequent formation into a sheet of randomly oriented carbon nanotubes. This ability to uniformly disperse individual nanotubes in a solvent can result in the production of a more planarly uniform nanotube film formed by removing the solvent from the suspended nanofibers. This physical uniformity can also improve the uniformity of properties (e.g., transparency to radiation) across the film.
[0042] As used herein, the term "nanofiber" refers to a fiber having a diameter of less than 1 μm. As used herein, the terms "nanofiber" and "nanotube" are used interchangeably and both include single-walled carbon nanotubes, double-walled carbon nanotubes, and / or multi-walled carbon nanotubes (where the carbon atoms are linked together to form a cylindrical structure).
[0043] In an example, the aqueous CNT suspension initially formed in operation 102 may have a purity of at least greater than 85% SWCNT. The remainder may be a mixture of DWCNT, MWCNT, and / or catalyst. In other examples, dispersed CNT suspensions may be prepared with different ratios of different types of CNT, such as about 20% / 75% DWCNT / SWCNT, about 50% / 45% DWCNT / SWCNT, about 70% / 20% DWCNT / SWCNT (with the remainder being MWCNT). In an example, an anionic surfactant may be used as a catalyst in the suspension.
[0044] In operation 103, the CNT suspension is then further refined to remove any aggregated or stuck CNTs from the initial mixture. In an example, different morphologies of CNTs (undispersed or aggregated vs. well-dispersed) may be separated from the suspension by centrifugation. Centrifugation of the surfactant-suspended carbon nanotubes before proceeding to the next filtration step may help reduce the turbidity of the suspension solution to ensure full dispersion of the carbon nanotubes within the final suspension solution. However, aspects of the present disclosure are not limited in this respect and other separation methods or processes may be used.
[0045] In operation 104, the CNT supernatant from operation 103 is then filtered through a filtration membrane to form a CNT web (a continuous sheet of film of intersecting CNTs).
[0046] In an example, one approach to making a CNT film is to deposit nanotubes in a random pattern on a filter using water or other fluid. A uniformly dispersed CNT-containing mixture is passed or forced through the filter, leaving a nanotube structure layer on the filter surface. The size and shape of the resulting film is determined by the size and shape of the desired filtering area of the filter, while the thickness and density of the film are determined by the quantity of nanotube material used in the process and the permeability of the filtering membrane to the components of the input material, since the permeated components are captured on the filter surface. If the concentration of nanotubes dispersed in the fluid is known, the mass of nanotubes deposited on the filter can be determined from the amount of fluid passing through the filter, and the areal density of the film can be determined by dividing the nanotube mass by the total filtering area. The filter selected is usually not permeable to any CNTs.
[0047] The filter-formed CNT films can be combinations of SWCNTs, DWCNTs, and / or MWCNTs in different compositions.
[0048] The CNT film is then removed from the filtration membrane in operation 105. More specifically, the carbon nanofibers may be randomly crossed to form an interconnected network structure in a planar orientation to form a thin CNT film.
[0049] In operation 106, the lifted CNT film is then collected using a collector frame and transferred and mounted directly onto virtually any solid substrate (e.g., the pellicle boundary with the aperture defined). The CNT film is attached to the pellicle boundary and covers the aperture to form a pellicle. Mounting the transferred film onto a metal or silicon frame with an aperture as small as 1x1 cm may be useful. For practical EUV scanners, there is a high demand for much larger sized films. CNT film characterization (e.g., its mechanical strength, distortion test, transmission test, distortion at constant pressure or during pumping down condition) may be performed. A full-sized pellicle for EUV lithography scanning may require an extremely thin free-standing film (usually larger than 110x140 mm) based on current industry standards.
[0050] Exemplary embodiments of the present disclosure feature filtered CNT pellicle films that have a structure different from known prior art while exhibiting properties that meet or exceed EUV lithography requirements, including, without limitation, EUV transmission (EUVT), EUVT uniformity, low distortion, and mechanical strength (under pressure changes).
[0051] This pellicle film construction results in an extremely thin pellicle film that allows for very high EUVT (e.g., greater than 92%, 95%, or even 98%) while being extremely temperature resistant (e.g., resistant to temperatures in excess of 600° C.) and mechanically robust. In an example, the minimum EUVT can be 92% or greater.
[0052] Although the above disclosure has been shown with respect to CNTs and aqueous solutions, aspects of the disclosure are not so limited and different nanotubes (eg, boron nitride nanotubes (BNNTs)) may be used with the same principles.
[0053] The aforementioned thin films may be conformally coated by various methods, such as, but not limited to, e-beam, chemical vapor deposition, atomic layer deposition, spin coating, dip coating, spray coating, sputtering, DC sputtering, and RF sputtering. The material may be a metallic element, including any one of the following: silicon, SiO2, SiON, boron, ruthenium, boron, zirconium, niobium, molybdenum, rubidium, yttrium, YN, Y2O3, strontium, and / or rhodium. The material may be any one of a metal, a metal oxide, or a nitride. However, aspects of the present disclosure are not limited thereto, and a combination of materials may be used in the coating.
[0054] CNT pellicle microstructure To analyze the CNT pellicle film microstructure, carbon nanotube film samples were prepared following a standard transmission electron microscopy sample preparation guide. The resulting high-resolution transmission electron microscopy (HRTEM) was analyzed. A typical image at 700K magnification can show one to eight CNTs. The DiameterJ plug-in tool (National Institute of Standards and Technology) or similar analysis tool was applied to examine the HRTEM images. The number of walls for each CNT was counted. Typical results, along with other measurements, are shown in Table 1 below.
[0055] [Table 1]
[0056] As shown above, each of the CNT pellicle film samples exhibited approximately 51% or more DWCNT composition, with the remainder consisting of a combination of SWCNTs and MWCNTs. The average percentage of DWCNTs among all four samples equaled a value of more than 60%.
[0057] In another study, CNT pellicle films exhibited greater than 20% SWCNTs, greater than 75% DWCNTs, with the remainder composed of MWCNTs.
[0058] In addition to the above, it has been shown that SWCNTs can account for 20-40% of all CNTs in a CNT pellicle film, and that DWCNTs and MWCNTs can account for more than 50% and less than 10%, respectively, of all carbon nanotubes.
[0059] Representative analytical results for Samples A-G (from FIG. 2) indicate that the best mechanical strength is achieved when DWCNTs account for more than 50% of the total CNT content. More specifically, Samples A-G in FIG. 2 illustrate the mechanical attribute values for DWCNT-dominated CNT pellicle films.
[0060] As illustrated in Figure 2, the DWCNT-dominated CNT pellicle films provide significantly higher burst pressure values compared to the SWCNT pellicle films (see sample H). More specifically, the DWCNT-dominated CNT pellicle films include burst pressure values ranging from approximately 136.0 Pa to 203.6 Pa, while the SWCNT pellicle film has a burst pressure of 66.6 Pa, less than half of the lowest burst pressure value of the DWCNT-dominated CNT pellicle films.
[0061] Additionally, it can be seen in Figure 2 that the DWCNT-dominated CNT pellicle films exhibit significantly lower strain values at a pressure of 2 Pa. In one case, the strain value of the DWCNT-dominated CNT pellicle film sample (0.047 mm) is nearly half that of the SWCNT pellicle film (0.097 mm). The lower strain value allows the CNT pellicle film to stay within the allowed space in the EUV lithography scanner.
[0062] Finally, Figure 6A (200K magnification) illustrates a set of bar graphs showing the diameters of different samples of DWCNT-major composition films according to exemplary embodiments, and Figure 6B (100K magnification) illustrates a set of bar graphs showing the major pore axes of different samples of DWCNT-major composition films according to exemplary embodiments.
[0063] Figures 6A and 6B illustrate typical distributions of various CNT bundle sizes and pore sizes of various DWCNT-rich film samples based on SEM image analysis. As illustrated in Figure 6A, the average bundle sizes for three separate samples are 18.7±10.5 nm, 12.8±6.9 nm, and 12.1±7.5 nm, respectively. Furthermore, as illustrated in Figure 6B, the average pore sizes for three separate samples are 38.911±35.011 nm, 42.286±36.826 nm, and 40.535±35.906 nm, respectively.
[0064] Thin Film Thickness Exemplary embodiments of the present disclosure are further analyzed for their thickness, which is important to determine and ensure high EUVT. More specifically, the Dimension Icon AFM instrument was first calibrated against a National Institute of Standards and Technology (NIST) traceable standard. CNT pellicle films with an area of approximately 90 μm×90 μm were selected for AFM 2D and 3D height imaging. Step height analysis was performed to measure the film thickness. Three measurements were performed from three carbon nanotube film samples, with readings of 11.8 nm, 10.6 nm, and 11.4 nm, respectively. The average thickness of the test objects was about 11.3±0.6 nm.
[0065] Furthermore, thickness values of 3 nm to 100 nm, 3 nm to 40 nm, and 3 nm to 20 nm were obtained based on additional sets of measurements.
[0066] Additionally, in other samples, the thickness values may be 3 nm to 100 nm, 3 nm to 40 nm, and 3 nm to 20 nm, but the embodiments of the present application are not limited thereto, and the range may be 3 nm to 5 nm at the lower end and 20 nm to 100 nm at the upper end.
[0067] Given the much higher mechanical strength exhibited by DWCNT-dominant CNT pellicle films, it may be possible to construct DWCNT-dominant CNT pellicle films extremely thin to obtain higher EUVT values without sacrificing mechanical strength or integrity for use in EUV scanners.
[0068] Visible and EUV transmittance The EUV transmittance of the samples was measured using the current industry standard 13.5 nm wavelength. EUVT maps were generated based on the EUV scanning results to demonstrate and measure the variation and / or uniformity of the transmittance.
[0069] We performed EUV transmittance measurements and pellicle life tests under high-intensity EUV irradiation of the samples. The EUV irradiation was performed at an irradiation intensity of 5.1 w / cm 2 (corresponding to the intensity on the EUV mask when using a 250 W light source) and introducing 5 Pa of hydrogen gas. The total EUV dose in this test was 73 kJ / cm 2 , which equates to processing approximately 14,000 wafers.
[0070] The filtered CNT pellicle films generally showed high EUV transmission, over 92%, with some results being over 95% or even under 98%. See, for example, FIG. 5A. For example, a full sample scan of a full-sized pellicle film (approximately 110mmx144mm) shows an average of 96.69±0.15% transmission, and a scan of the 1.5mmx1.5mm central area gives an average of 96.75±0.03% transmission. A very strict criterion for evaluating EUVT uniformity is used to calculate the difference between any two EUVT measurements from the same nanostructured film at any focal area. This requirement can be less than 5%, less than 2%, or even less than 1.0% or less. For the full-sized pellicle of this exemplary embodiment, the multi-point EUVT uniformity test results (100 points measured per sample) show some very small variations of less than 1.5%, less than 0.9%, less than 0.6%, or less than 0.4%.
[0071] 5 illustrates the EUV transparency, reflectance, and scattering of a filtered CNT pellicle film according to an exemplary embodiment. More specifically, FIG. 5A illustrates a 1×1 cm 2 Size 2 0.6μg / cm 2 FIG. 5B illustrates a linear map of EUV transparency of a film of 1×1 cm 2 in accordance with an exemplary embodiment. 2 Size 2 0.6μg / cm 2 1 illustrates a linear map of EUV reflectance of a film.
[0072] As illustrated in FIG. 5, the filtered CNT pellicle film has an EUV transparency of over 97% with exceptionally low reflectance and scattering levels of 0.21%. More specifically, FIG. 5A illustrates EUVT values of 97%-99% for both Samples A and B, with the majority of the EUVT values being 98%-99%. As illustrated in FIG. 5A, the CNT pellicle film provided in the present disclosure provides very high EUVT values that have not been achieved before. Given the high EUVT values, as seen in FIG. 5B, the CNT pellicle film has very low reflectance values, with the majority of the values being below 0.00005 mm, and almost all of the values being below 0.00010 mm. Based on the foregoing, given the very high EUVT values and very low reflectance values, it can be seen that the CNT pellicle film, with the majority of the structure (at least 50%) being DWCNT, transmits almost all of the EUV radiation.
[0073] Furthermore, the areal density of the CNT pellicle film affects the visible light transmittance and visible light absorbance. In this regard, FIG. 4A illustrates the transparency and absorbance of a DWCNT film at 550 nm (e.g., visible light) for different areal densities according to an exemplary embodiment.
[0074] As typically illustrated in Figure 4A(I), there is an inverse relationship between areal density and 550 nm wavelength transmittance. The inverse relationship is typically illustrated in Figure 4A(II). At one end, an areal density of 0.62 μg / cm 2gives an average transmittance value of 93.833% at 550 nm wavelength. At the opposite end, the areal density is 3.11 μg / cm 2 results in an average transmittance value of 72.900% at a wavelength of 550 nm.
[0075] On the other hand, there is a direct relationship between areal density and absorbance. The direct relationship is typically illustrated in Figure 4A(III). At one end, an areal density of 0.62 μg / cm 2 gives an average absorbance value of 0.028. At the opposite end, the areal density is 3.11 μg / cm 2 results in an absorbance value of 0.137.
[0076] Mechanical properties of CNT pellicles for EUV Exemplary embodiments of the present application provide a CNT pellicle with sufficient and satisfactory mechanical strength for product transportation and handling. The pellicle can sustain any desired pressure change surrounding its environment (e.g., without limitation, an EUV lithography scanner environment).
[0077] A widely applied mechanical characterization has been the bulge test. For example, the membrane under test may be mounted on a flat surface of the interface, and a baseline of the membrane may be established. An initial flow of inert gas may then be applied perpendicularly at a low, steady pressure aimed at the central region of the membrane to raise the local surface. The gas pressure is gradually increased to further deform the membrane until the pressure reaches a predetermined value (2 Pascal for 2 Pa strain test), which may be under a flow rate of about 10 sccm, 3.5 mbar / sec, or any scanner pump-down condition. The distance between the highest tip of the deformed membrane and its baseline may be measured. The results may be recorded as strain at 2 Pa. Strain tests may also be performed at various pressures other than 2 Pa.
[0078] Increasing the gas flow pressure may eventually cause the membrane to burst, which may be recorded as the burst pressure, and the membrane strain just prior to bursting may be referred to as the burst strain.
[0079] Additionally, thin film strain may be deliberately adjusted by methods such as, but not limited to, tension adjustment by physical or chemical means.
[0080] FIG. 4B illustrates the effect of areal density on strain at constant 2 Pa pressure and burst for a DWCNT-dominated film of size 10×10 mm according to an exemplary embodiment. FIG. 4C illustrates the effect of areal density on strain at constant 2 Pa pressure and burst strain for a film of size 10×10 mm and 2.9-3.0 μg / cm. 2 FIG. 4D illustrates the effect of MWCNT concentration on areal density versus 2 Pa and DWCNT film strain at rupture for a film 110×140 mm and 0.65 μg / cm during pumping down at the highest rate of 3.5 mbar / sec according to an exemplary embodiment. 2 4A illustrates the distortion of areal density. FIG 4E illustrates the burst pressure of films for various DWCNT / MWCNT ratios providing evidence supporting the current embodiment.
[0081] The structure of the film may be highly porous. See, for example, Figures 3A and 3B. It may also be highly dependent on the areal density. More specifically, the film may be so porous that the areal density (μg / cm) may be used instead of the film thickness. 2 ) may be used. This change in microstructure also greatly affects the mechanical properties of the film (Figure 4B). In addition, visible light absorption is also affected. These films appear to observe the Beer-Lambert law quite well in the range measurements. See, for example, Figure 4A. In the example, CNT pellicle films (including full-size films) have areal densities from about 0.2 μg / cm2 to about 6.0 μg / cm2. 2 It could be.
[0082] Based on strain testing of full-sized CNT pellicles of exemplary embodiments, the network CNTs making up the CNT film can have strains of less than 4.0 mm, 3.0 mm, 1.5 mm, or even less than 0.6 mm under a constant 2 Pa pressure.
[0083] Membranes of various sizes were tested (from 1 cm x 1 cm up to 12 cm x 15 cm), however, aspects of the present disclosure are not so limited and testing of other sizes not specified herein may be possible.
[0084] The microstructure of BNNT films is somewhat similar to that of CNT films, but has a lower aspect ratio and contains more impurities due to the nature and lower purity of the available raw materials.
[0085] Low areal density CNT films can be produced for high EUV transmittance, but the films may be highly sensitive to changes in their external pressure. By increasing the areal density of the CNT film, the film may have very little strain at constant pressure and may have a slightly increased elongation at the burst point. See, for example, Figure 4B.
[0086] As typically illustrated in Figure 4B(I), 0.62 μg / 2 on the low areal density side results in an average distortion value of 0.098 mm at a pressure of 2 Pa. On the other hand, 3.11 μg / 2 on the high areal density side results in an average distortion value of 0.012 mm at a pressure of 2 Pa. The inverse proportional relationship between areal density and distortion value at 2 Pa is typically illustrated in Figure 4B(II).
[0087] Figure 4B(I) also demonstrates the nearly direct relationship between areal density and strain at rupture for the CNT film. For example, 0.62μg / 2 on the low areal density side results in an average strain at rupture of 0.289mm, whereas 3.11μg / 2 on the high areal density side results in an average strain at rupture of 0.380mm. The relationship between areal density and strain at rupture is typically illustrated in Figure 4B(III).
[0088] However, the fundamental EUV transparency capabilities may be affected, ultimately rendering such high areal density films unusable for EUV lithography.
[0089] The effect of the type of CNT used (i.e., MWCNT) is shown in Figure 4C. MWCNT films show higher strains at the same pressure than DWCNT films, lower Young's modulus of the film material (softer) and lower strain at rupture indicating lower elongation at rupture (more brittle). An explanation for this could be that at the same areal density, films made with MWCNT have a lower total nanotube length per area than films made with DWNCT, which means there are fewer contact points between the nanotubes, which could lead to a weaker material.
[0090] More specifically, FIG. 4C(I) illustrates the average strain value and maximum strain value at a pressure of 2 Pa for various CNT film samples having different composition ratios of DWCNT and MWCNT. As shown in FIG. 4C(I), the CNT film consisting of 100% DWCNT has an average strain value of 0.030 mm and a maximum strain value of 0.379 mm at a pressure of 2 Pa. Furthermore, the CNT film consisting of 75% DWCNT and 25% MWCNT has an average strain value of 0.029 mm and a maximum strain value of 0.345 mm at a pressure of 2 Pa. The CNT film consisting of 50% DWCNT and 50% MWCNT has an average strain value of 0.052 mm and a maximum strain value of 0.336 mm at a pressure of 2 Pa. The CNT film consisting of 25% DWCNT and 75% MWCNT has an average strain value of 0.072 mm and a maximum strain value of 0.307 mm at a pressure of 2 Pa. Finally, the CNT film consisting of 100% MWCNT has an average strain value of 0.066 mm at 2 Pa pressure and a maximum strain value of 0.300 mm. As illustrated in FIG. 4C(I), the strain value at 2 Pa pressure generated by 100% MWCNT (i.e., 0.066 mm) is more than twice the strain value at 2 Pa pressure for 100% DWCNT (i.e., 0.030 mm). The direct relationship between the strain value at 2 Pa pressure and the MWCNT composition ratio is illustrated in FIG. 4C(II). The inverse relationship between the maximum strain value and the MWCNT composition ratio is illustrated in FIG. 4C(III).
[0091] Essentially, the pure DWCNT films exhibit higher mechanical strength. Figure 4E shows the burst pressure (Pa) for various ratios of DWCNT to MWCNT. All films had similar areal density and transparency. DWCNT is significantly stronger than MWCNT.
[0092] FIG. 2 illustrates that CNT films consisting primarily of single-walled carbon nanotubes have significantly different values than CNT films whose majority composition is double-walled carbon nanotubes. FIG. 2 further illustrates that the average strain value of 0.0967 mm measured at 2 Pa for the DWCNT-dominated CNT film is nearly twice the lower range value of 0.0473 mm for the SWCNT film. Furthermore, the SWCNT film exhibits a much lower average burst pressure of 66.61 Pa. Finally, an average burst strain of 0.498 mm is obtained for the DWCNT-dominated CNT film, compared to 0.097 mm for the SWCNT film. Also in FIG. 2, a composite MWCNT film of comparable size also shows its weakness in burst pressure and strain compared to the DWCNT-dominated CNT film.
[0093] As typically illustrated in FIG. 2, CNT films composed mostly of DWCNTs (e.g., at least 50%) have significantly lower strain with higher transmittance, and significantly higher burst resistance indicating higher structural strength.
[0094] Life Test 13A-CNT pellicle film according to an exemplary embodiment. 1x1cm 2 The CNT pellicle remains intact after EVU irradiation at a power of 5.1 w / cm 2 At a dose of 73 kJ / cm 2 was exposed to.
[0095] In addition, the power is 20w / cm 2 90kJ / cm for 4 hours 2EUV irradiation testing of a full-size CNT pellicle with a dose equivalent to 1000 nm (corresponding to a 600 watt energy source) demonstrated undestroyed CNT films. This test dose can correspond to the total dose required to process approximately 32,000 wafers.
[0096] As shown above, the inventors have demonstrated the feasibility of fabricating free-standing nanoparticle films with suitable dimensions to be used as EUV pellicles in an EUV scanner environment. When formed with a sufficiently thin single wall of CNT material, these films have high EUV transparency (e.g., greater than 92%), low scattering (e.g., less than 0.3%), and retain sufficient mechanical stability and porosity (e.g., less than 0.1 mm distortion at 3.5 mbar / sec pump down) to withstand the transport, handling, and pump-down operations for a full-sized EVU pellicle.
[0097] Furthermore, the film withstands EUV irradiation at doses and powers equivalent to 250W to 600W EUV scanners.
[0098] The illustrations of the embodiments described herein are intended to provide a general understanding of the various embodiments. The illustrations are not intended to serve as a complete description of all of the elements and features of the products and methods constituting the products or methods described herein. Many other embodiments may become apparent to those skilled in the art upon review of the present disclosure. Since other embodiments may be utilized and derived from the present disclosure, structural and logical substitutions and changes may be made without departing from the scope of the present disclosure. Furthermore, the illustrations are merely representative and may not be drawn to scale. Certain proportions within the illustrations may be exaggerated, while other proportions may be minimized. Thus, the present disclosure and figures should be considered illustrative rather than limiting.
[0099] One or more embodiments of the present disclosure may be referred to herein, individually and / or collectively, by the term "invention" merely for convenience and without any intention to spontaneously limit the scope of the present application to any particular invention or inventive concept. In addition, although specific embodiments have been illustrated and described herein, it will be understood that any subsequent arrangements designed to achieve the same or similar purpose may be substituted for the specific embodiment shown. The present disclosure is intended to cover any and all subsequent adaptations or variations of the various embodiments. Combinations of the foregoing embodiments, as well as other embodiments not specifically described herein, will be apparent to one of ordinary skill in the art upon review of this description.
[0100] The Abstract of the Disclosure is submitted with the understanding that it will not be used to interpret or limit the scope or meaning of the claims. In addition, the foregoing Detailed Description may group or describe various features together in a single embodiment for the purpose of streamlining the disclosure. This disclosure should not be interpreted as reflecting an intention that the claimed embodiments require more features than are expressly recited in each claim. Rather, as the following claims reflect, inventive subject matter may be directed to less than all of the features of any of the disclosed embodiments. Thus, the following claims are incorporated into the Detailed Description, with each claim standing on its own as defining separately claimed subject matter.
[0101] The foregoing disclosed subject matter should be considered as illustrative and not limiting, and the appended claims are intended to cover all such modifications, extensions, and other embodiments that fall within the true spirit and scope of the present disclosure. Accordingly, to the maximum extent permitted by law, the scope of the present disclosure should be determined by the broadest permissible interpretation of the following claims and their equivalents, and should not be limited or restricted by the foregoing detailed description.
Claims
1. 1. A nanostructured film comprising: a plurality of carbon nanofibers randomly crossing to form an interconnected network structure in a planar orientation, the interconnected network structure comprising the plurality of carbon nanofibers having a thickness ranging from a lower limit of 3 nm to an upper limit of 100 nm and having a plurality of pores; the plurality of carbon nanofibers includes single-walled carbon nanotubes, multi-walled carbon nanotubes, and at least 50% double-walled carbon nanotubes; A nanostructured film, wherein the single-walled carbon nanotube has one wall, the double-walled carbon nanotube has two walls, and the multi-walled carbon nanotube has three or more walls.
2. 10. The nanostructured film of claim 1, wherein said plurality of pores have a pore diameter between 3.9 nm and 79.112 nm.
3. 2. The nanostructured film of claim 1, wherein said thickness is from said lower limit of 3 nm to an upper limit of 40 nm.
4. 2. The nanostructured film of claim 1, wherein said thickness is from said lower limit of 3 nm to an upper limit of 20 nm.
5. 10. The nanostructured film of claim 1, wherein the interconnected network structure has an average thickness of 11 nm.
6. 2. The nanostructured film of claim 1, wherein, of said plurality of carbon nanofibers, said single-walled carbon nanotubes account for 20-40%; said double-walled carbon nanotubes account for 50% or more; and the remaining carbon nanotubes are said multi-walled carbon nanotubes.
7. 10. The nanostructured film of claim 1, wherein, of said plurality of carbon nanofibers, said single-walled carbon nanotubes account for more than 20% of said plurality of carbon nanofibers, said double-walled carbon nanotubes account for more than 75% of said plurality of carbon nanotubes, and the remaining carbon nanotubes are said multi-walled carbon nanotubes.
8. 10. The nanostructured film of claim 1, wherein any two EUV transmission measurements from the same nanostructured film in any EUV transmission measurement area differ by less than 5%.
9. 10. The nanostructured film of claim 8, wherein any two EUV transmission measurements from the same nanostructured film in any EUV transmission measurement area differ by less than 2%.
10. 10. The nanostructured film of claim 9, wherein any two EUV transmission measurements from the same nanostructured film in any EUV transmission measurement area differ by less than 0.4%.
11. 10. The nanostructured film of claim 1, wherein said interconnected network structure has a distortion of less than 3.5 mm under a flow rate of 10 sccm of inert gas when said interconnected network structure has a full size of at least 140 mm x 110 mm.
12. 12. The nanostructured film of claim 11, wherein said distortion is less than 0.6 mm under a flow rate of 10 sccm of inert gas.
13. 10. The nanostructured film of claim 1, wherein the interconnected network structure has a distortion of less than 3.5 mm under a flow rate of 3.5 mbar / sec of inert gas when the interconnected network structure has a full size of at least 140 mm x 110 mm.
14. 14. The nanostructured film of claim 13, wherein the interconnected network structure has a distortion of less than 0.6 mm under a flow rate of inert gas of 3.5 mbar / sec when the interconnected network structure has a full size of at least 140 mm x 110 mm.
15. 10. The nanostructured film of claim 1, wherein the interconnected network structure has a distortion of less than 4.0 mm under 2 Pa pressure of inert gas when the interconnected network structure has a full size of at least 140 mm x 110 mm.
16. 10. The nanostructured film of claim 1, wherein the interconnected network structure exhibits less than 0.3% scattering under EUV irradiation.
17. 10. The nanostructured film of claim 1, wherein the interconnected network structure is conformally coated with a metal, metal oxide, or nitride, the metal being selected from boron, ruthenium, zirconium, niobium, molybdenum, rubidium, yttrium, strontium, or rhodium.
18. The interconnected network structure has an areal density of 0.2 μg / cm 2 ~6.0 μg / cm 2 2. The nanostructured film of claim 1 , wherein:
19. A pellicle, a pellicle boundary defining an opening; at least one nanostructured film attached to the pellicle boundary and covering the opening; The at least one nanostructured film comprises: a plurality of carbon nanofibers randomly crossing to form an interconnected network structure in a planar orientation, the interconnected network structure comprising the plurality of carbon nanofibers having a thickness ranging from a lower limit of 3 nm to an upper limit of 100 nm and having a plurality of pores; the plurality of carbon nanofibers includes single-walled carbon nanotubes, multi-walled carbon nanotubes, and at least 50% double-walled carbon nanotubes; The pellicle, wherein the single-walled carbon nanotube has one wall, the double-walled carbon nanotube has two walls, and the multi-walled carbon nanotube has three or more walls.
20. The pellicle of claim 19, wherein the plurality of pores have a pore diameter of 3.9 nm to 79.112 nm.
21. 20. The pellicle of claim 19, wherein the opening in the pellicle boundary is 140 mm x 110 mm and the at least one nanostructured film has a distortion of less than 3.5 mm under a flow rate of inert gas of 3.5 mbar / sec.
22. 20. The pellicle of claim 19, wherein the opening at the pellicle boundary is 140 mm x 110 mm and the at least one nanostructured film has a deflection of less than 4.0 mm under 2 Pa pressure.
23. 1. A method of performing EUV lithography comprising transmitting EUV radiation through a pellicle, comprising: the pellicle includes a pellicle boundary defining an opening, and at least one nanostructured film attached to the pellicle boundary and covering the opening; The at least one nanostructured film comprises: a plurality of carbon nanofibers randomly crossing to form an interconnected network structure in a planar orientation, the interconnected network structure comprising the plurality of carbon nanofibers having a thickness ranging from a lower limit of 3 nm to an upper limit of 100 nm and having a plurality of pores; the plurality of carbon nanofibers includes single-walled carbon nanotubes, multi-walled carbon nanotubes, and at least 50% double-walled carbon nanotubes; The method, wherein the single-walled carbon nanotube has one wall, the double-walled carbon nanotube has two walls, and the multi-walled carbon nanotube has three or more walls.
24. The method of claim 23, wherein the plurality of pores have a pore diameter between 3.9 nm and 79.112 nm.
Citation Information
Patent Citations
Pellicle, method for producing pellicle and exposure method using the pellicle
JP2017083791A
Method for forming pellicle
JP2018194838A
Induced stress for EUV pellicle tensioning
JP2020101788A
JPP7392184B
Pellicle for exposure to extreme ultraviolet light, photomask assembly, and method of manufacturing the pellicle
US20180284599A1
Cited By
Nanostructure film, pellicle, and method of performing EUV lithography
JP2025076488A